1984
DOI: 10.1144/gsjgs.141.1.0105
|View full text |Cite
|
Sign up to set email alerts
|

MOIST and the continuity of crustal reflector geometry along the Caledonian-Appalachian orogen

Abstract: New aspects of the deep structure of the Scottish Caledonides are revealed by the Moine and Outer Isles deep seismic reflection traverse (MOIST). The Caledonian foreland is underlain by an easterly-dipping, strongly reflecting surface cutting through the Moho and traceable to more than 45 km depth. Thrusts within the foreland basement and Caledonian orogen have been reactivated as normal faults bounding half-grabens filled with sediments of late Palaeozoic to Mesozoic age. The Moine Thrust, which carries rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(95 citation statements)
references
References 22 publications
2
92
1
Order By: Relevance
“…A thick-skinned style is in effect confirmed by seismic profiling of MOIST [151] where the upper crust contains several reflections, which are interpreted as thrust faults that sole into a horizontal reflection band at a depth of around 20 km. However it is not clear yet if these imbricate thrusts are in the hanging wall of the Moine thrust -in which case the Moine thrust would root at around 20 km depth -or if these imbricate thrusts are in the footwall of the Moine thrust.…”
Section: Caledonidesmentioning
confidence: 78%
“…A thick-skinned style is in effect confirmed by seismic profiling of MOIST [151] where the upper crust contains several reflections, which are interpreted as thrust faults that sole into a horizontal reflection band at a depth of around 20 km. However it is not clear yet if these imbricate thrusts are in the hanging wall of the Moine thrust -in which case the Moine thrust would root at around 20 km depth -or if these imbricate thrusts are in the footwall of the Moine thrust.…”
Section: Caledonidesmentioning
confidence: 78%
“…As indicated in Section 5 of this paper, such a material will not localise during deformation unless softening occurs. Localisation in exposed lower crustal materials is ubiquitous (see for instance, Ramsay, 1974) and seismic profiling of the lower crust commonly reveals localisation of deformation (see for instance, Brewer and Smythe, 1984). This means that we need to understand softening mechanisms in viscous materials or address the issue that perhaps lower crustal materials also have a plastic component to their constitutive behaviour so that localisation controlled by yield-surface corner behaviour (see Rudniki and Rice, 1975) or other yield associated behaviour (see Vermeer and de Borst, 1984) can be incorporated into realistic models of the Earth's crust.…”
Section: Breakdown Of the Linear Byerlee Relationshipmentioning
confidence: 99%
“…Thus Enfield & Coward (1987) showed that the West Orkney basin preferentially reactivated the Caledonian deformation fabric, as imaged in the MOIST deep seismic data (e.g. Brewer & Smythe 1984). This was not simply reactivation of pre-existing faults.…”
Section: Basin Evolutionmentioning
confidence: 84%